The Relationship Between Knee Function After ACL Reconstruction And Physical Activity Level Of The ACL Community Indonesia - Vinzenza Villia Ardike Bondeng; I Putu Gde Surya Adhitya (Masker Medika, 2024)
Background: Several deficits occurred in the knee after ACL reconstruction that affected the level of physical activity. The purpose of this study was to determine the relationship between post-ACLR knee function and physical activity level. Methods: The design of this study was observational analytic using a cross-sectional approach. The total sample consisted of 105 people from the Indonesian ACL Community selected using purposive sampling technique. Research instruments used to measure knee function included the Knee Injury and Osteoarthritis Outcome Score (KOOS) and Lysholm Knee Scale, while physical activity was assessed using the Tegner activity scale (TAS). Results: A relationship was found between post-ACLR knee function and physical activity, with the results of the Spearman's rho test indicating a value of p = 0.034 (p <0.05) and a value of r = 0.207, which was positive. A positive value indicated that knee function increased or improved, leading to a tendency for increased physical activity. Discussion: Impaired knee function after ACLR negatively affected the level of physical activity, emphasizing the importance of special attention to knee function rehabilitation to optimize physical activity and achieve satisfactory results. Keywords: Anterior Cruciate Ligament Reconstruction, Knee Function, Physical Activity, Knee Injury and Osteoarthritis Outcome Score, Lysholm Knee Scale, Tegner activity scale.